Study on fuzzy GIS for navigation safety of fishing boats. Issue 2 (4th May 2017) - Kao, Sheng-Long; Chang, Ki-Yin
ABSTRACT: Maritime ship collisions involving fishing boats have often been reported, and the major factors have been human error and unpredictable conditions. This paper aims to create a set of collision-avoidance measures for operating fishing boats or a vessel traffic service by way of time and space management. It proposes a novel safe collision-avoidance safeguarding ring for navigational safety between operating fishing boats and merchant ships with a dummy automatic identification system (AIS) to enable fishing boats to establish a dynamic state when approaching ships under operation (fishing). The approach method utilises the maximum relative speed, sea state, and escape time as three linguistic input variables for fuzzy logic control application. After the radius of the safeguarding ring is obtained and shown on a marine geographic information systems (MGIS) platform, the danger index of two ships is evaluated based on the area difference calculated through the MGIS. The software was installed in the dummy AIS receivers of fishing boats for experimentation in a Taiwan harbour. It was able to enhance the collision-avoidance ability of the operating fishing boats effectively and reduce marine disasters involving fishing boats.